Integration of Solar Power Plant in Distribution Network - Srete N. Nikolovski; Predrag Ž. Marić; Ljubomir V. Majdandžić (International Journal of Electrical and Computer Engineering (IJECE), 2015)
This paper presents the integration of the solar power plant SE Gumiimpex, rated power of  1 MW in Croatian distribution network. Basic data of solar power plant are presented as well as the analysis of its impact on the distribution network. Power quality measurements, seven days before and seven days after the connection of PV plant to the grid are performed and obtained power quality indices are compared to those stated in the power quality standard HRN EN 50160/2012 and Croatian grid code. There are also presented results of the simulation of protection relays selection and coordination